Functionality of the nursing, management and administration research groups - Erdmann, Alacoque Lorenzini; Mello, Ana Lúcia Ferreira de; Andrade, Selma Regina de; Klock, Patrícia (Rev Rene, 2010)
The aim of this study is to understand the modes of organization and operation of the Nursing Management Research Groups (RG), registered in the Brazilian National Research and Science Council (BNRSG). It was used the methodological referential of the theory based on data and 12 leaders of research groups were interviewed. They were distributed in 2 sample groups. The functionality of the groups is understood as the way the activities of the research groups are structured. The most used theoretical-methodological contributions are the living experiences of the research, the intra-group relationships, the leader’s of RG role facing difficulties as well as the survival strategies that guarantee the longevity and productivity of the RG. The functionality of the research groups is a reflex of qualifying, legitimating, increasing and congregating potencies for the productivity in research lines and the researchers’ leadership in this area.